Pediatric achalasia. Single-center study of interventional treatment - Andrzej Grabowski; Wojciech Korlacki; Michał Pasierbek; Roksana Pułtorak; Filip Achtelik; Maciej Ilewicz (Gastroenterology Review)
Introduction: Esophageal achalasia is a rare entity in children. However, young age is a factor of failure of conservative treatment, emphasizing the role of surgery. In our institution laparoscopic Heller’s cardiomyotomy is the chosen procedure for surgical treatment. Aim: To assess the outcome of surgery for achalasia treatment in children operated on in a single institution. Material and methods: A retrospective analysis of consecutive patient records from the years 1997 to 2014 was performed. There were 11 patients. Their mean age was 13 years, ranging from 6 to 17. Duration of symptoms was 2 to 36 months, mean 16. All 11 patients were operated on with a laparoscopic approach. Pneumatic dilatation was used both pre- and postoperatively but in no case was sufficient on its own. Collected data included patient demographics, preoperative symptoms and their duration, diagnostic findings and therapeutic means. Surgical procedures, complications and long-term follow-up were analyzed. The follow-up lasted from 1 to 10 years and finished when the patient reached 18 years of age. Results: Twelve laparoscopic cardiomyotomies were performed with concomitant fundoplications, 10 Toupet and 2 Dor and one redo procedure. There were no deaths. Two perforations were repaired promptly. The success rate was 82%, though with subsequent dilatations. One failure was due to serious progression of the disease. Conclusions : In our opinion, laparoscopic Heller’s myotomy is the procedure of choice for treating achalasia in children. Endoscopic balloon dilatation may be used as a complementary treatment, especially as a primary redo procedure.